Narrative Exposure Therapy in Patients With Posttraumatic Stress Disorder and Borderline Personality Disorder in a Naturalistic Residential Setting: A Randomized Controlled Trial - Steuwe, Carolin; Berg, Michaela; Beblo, Thomas; Driessen, Martin (Frontiers in Psychiatry, 2021)
Background. Comorbid Posttraumatic Stress Disorder (PTSD) increases the already high symp-tom burden of patients with Borderline Personality Disorder (BPD). As the gold standard for BPD treatment, Dialectical Behavior Therapy (DBT), does not focus on PTSD, other treatment approaches are needed. Narrative Exposure Therapy (NET) was designed to address multiple traumatic events and may be especially useful in this patient group. The aim of the present study was to determine the efficacy of NET compared to DBT based treatment (DBT-bt) in a random-ized controlled trial. Methods. Female patients (n=60) with BPD and comorbid PTSD were randomized to either a 10-week residential NET or DBT-bt. The primary outcome was change in PTSD severity as assessed by the Clinician Administered PTSD Scale (CAPS). Mixed linear models as well as reliable change, remission and response rates were used to compare improvement across treatment groups. Results. Mixed linear model showed that patients in both treatments improved significantly over time across all outcome measures. This improvement was not more pronounced in NET (no sig-nificant time x type of treatment effect). However, NET resulted in a higher remission rate as compared to DBT-bt. PTSD remission was accompanied by BPD remission in all cases. Conclusions. This study shows the value of trauma-focused therapy in patients with BPD and PTSD for recovery in both disorders. To shorten the duration of both illnesses as much as possi-ble, future studies should focus on the factors predicting treatment success and enabling patients to benefit from trauma-focused treatment as soon as possible.